Green chemistry approaches in the analytical validation of fosravuconazole using UV spectrophotometry and HPLC - Jeswin Maliyakal; Mital Patel (Green Analytical Chemistry)
Fosravuconazole, a newly developed oral antifungal medication by Eisai, has been utilized since 2018 for the treatment of tinea unguium. Its notable characteristics include high oral absorption and systemic bioavailability, which allow for a brief treatment duration of 3 months. Its mild inhibition of the cytochrome P450 enzyme, which plays a role in adverse effects during polypharmacy, allows for the safe use of fosravuconazole alongside other medications, making it suitable for elderly patients. This study addresses the need for a precise quantitative method to determine “Fosravuconazole” using UV spectrophotometry and High-Performance Liquid Chromatography (HPLC). The HPLC method used an isocratic approach with a reversed-phase CHROMASIL C18 column (4.6 mm × 250 mm, 5 µm), a flow rate of 0.9 mL/min and detection at a wavelength of 287 nm. The mobile phase was a mixture of Acetonitrile and a 10 mM Ammonium Acetate buffer at pH 4.5, with the pH adjusted using acetic acid. Both methods were rigorously validated according to ICH Q2(R1) guidelines, demonstrating their suitability for the assessment of individual substances in various mixtures. To evaluate their environmental impact, AGREE, GAPI, and BAGI were used to evaluate the methods highlighting their sustainability in terms of solvent consumption, chemical and energy use, waste generation. BAGI showed that both methods possess scores above the recommended threshold score of 60, qualifying them for industrial applications. The UV method demonstrated a greener profile compared to the HPLC method.